Pemberdayaan Perempuan Berbasis Pesantren dan Social Entrepreneurship - Prasetiyawan, Arian Agung; Rohimat, Asep Maulana (IAIN Pekalongan, 2019)
The purpose of this study is to describe the model of empowerment of women based on pesantren and social entrepreneurship. When women are still underestimated in the world of entrepreneurship, it is hoped that the pesantren-based social entrepreneurship model will be the solution. Because pesantren are now deeply rooted in the midst of Indonesian society, and there are very many in almost every region of the archipelago. thus it has enormous potential to provide solutions to current gender biases, especially in the development of female entrepreneurs.This research is a qualitative field research with descriptive analytic methods, literature study, reviewing documents, direct observation to the location, and interviews with related parties conducted by researchers to search for data sources. The Ethnographic Study that we carried out took the form of in-depth interviews with managers and members of Catering Ummahat Modern As Salam Surakarta Islamic Boarding School, which in fact they were women, even among them were widowed. In addition, we also conduct literature studies that are relevant to this research.The findings obtained are that the empowerment of women based on pesantren has been carried out in this ummahat catering business institution, using the empowerment model of widowed, disadvantaged, and former lay-off women. The result is they get material income for their lives which makes them more prosperous and happy. Also as a form of social entrepreneurship in the form of profit sharing from entrepreneurs they distribute to Zakat, infaq and alms and social benefits and skills development practices for members.